Prison nursing: legal framework and care reality - H. Carrasco-Baún
Introduction: Penitentiary Nursing has experienced during the last decades a deep transformation similar to that experienced by the rest of the Nursing. However, there is a great distance from the protective legislation. Objective: To analyze the main legal documents which regulate the functions of Penitentiary Nursing and to compare it with the health care reality of nurses in Spanish prisons. Methodology: Narrative bibliographic review based on various sources such as Medline, Cuiden, Scielo, Dialnet, etc. Results: Is selected 43 documents, due to its relevance with the theme object of study. Is rejected 4 articles for lack of the same. Analyzed documents regarding legal framework and functions of nursing in prisons in its different sections (health care, teaching, research and management). Conclusion: The functions currently carried out in prisons are the ones provided for by health care legislation outside the prison context, along with the internal administrative regulations established by prisons. The possibility should be reconsidered of integrating Prison Healthcare into the Public Healthcare System so as to guarantee equality of healthcare for persons deprived of liberty and to provide the same rights and obligations to health professionals working in this sector.